Multi-functional liposomes showing radiofrequency-triggered release and magnetic resonance imaging for tumor multi-mechanism therapy. Issue 12 (28th March 2015) - Du, Bin; Han, Shuping; Li, Hongyan; Zhao, Feifei; Su, Xiangjie; Cao, Xiaohui; Zhang, Zhenzhong
<x xml:space="preserve">Abstract</x> Schematic illustration of design of functional liposomes showing radiofrequency-triggered drug release (A) and RF targeted thermo-chemotherapy using the nanocomposite (B).